REDESIGN OF 5 FLOOR HOTEL EARTHQUAKE RESISTANT BUILDING WITH SWIMMING POOL ON ROOFTOP - Hizqi Rahmawati; Endah Kanti Pangestuti (DAS Institute, 2022)
The increase in the number of earthquake cases in Indonesia goes hand in hand with an increase in population and land requirements. This is a particular concern for structural experts in planning buildings vertically to save space. Therefore earthquake-resistant building planning is needed. The design of a building with a swimming pool on the top level of the building, especially on the roof floor, has become one of the trends in society, commonly known as an infinity pool. Structurally, a building with a swimming pool on the top floor must be given special attention. The swimming pool on the top floor, especially on the roof floor of the building, unquestionably burdens the building. In planning for earthquake-resistant buildings, it refers to the latest SNI, namely SNI 1726: 2019 Procedures for Planning for Earthquake Resistance for Building and Non-Building Structures and 2847: 2019 Requirements for Structural Concrete for Buildings and Explanations